Two new names in Holothrix (Orchideae, Orchidaceae) - Bytebier, Benny; Le Péchon, Timothée (Phytotaxa, 2021)
Le Péchon et al. (2019) found that Bartholina Brown in Aiton (1813: 194) is deeply embedded in Holothrix Richard in Lindley (1835: 257). Holothrix includes around 46 species with the highest diversity in southern and eastern Africa, whereas Bartholina includes only two species endemic to the Greater Cape Floristic Region (WCSP, 2021). Bartholina predates Holothrix, and to preserve nomenclatural stability, a proposal for conservation has been published (Le Pechon & Bytebier, 2019), and so we would like to make the new names in Holothrix available.